المفردات الاصطلاحية في كتاب توضيح الأحكام الجزء الثالث والاستفادة منها في إثراء اللغة العربية لدى الطالبات بجامعة الراية - WA ODE AFILA; ARIF TAUFIKURRAHMAN (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2016)
Indeed, the reason for the weakness of students in enriching the Arabic language is the lack of knowledge of vocabulary, although the vocabulary has a significant impact in the development of the language of language learners, as the object increases his skills in the language if increased vocabulary. The objectives of this study are to know the conventional vocabulary in the book to clarify the provisions of the third chapter and to use them in enriching the Arabic language. The method of completion of this study was on the descriptive analytical method. This research was done by collecting vocabulary and analysis, and then explaining the meanings of these terms in terms of language and terminology based on some books and dictionaries. These words are written according to the subject in each chapter in the book explaining the provisions, to facilitate the learners of the Arabic language and teachers when they refer to the meanings of vocabulary related to it when learning and education or review. It is clear from this study that the conventional vocabulary that was collected reached 80 vocabulary and can be used to enrich the Arabic language in the students of the University of Ar-Raayah. In the manner of presenting vocabulary in the form of dialogue and the text of reading and exercises when they learn.